Can leptin-derived sequence-modified nanoparticles be suitable tools for brain delivery?. (March 2012) - Tosi, Giovanni; Badiali, Luca; Ruozi, Barbara; Vergoni, Anna Valeria; Bondioli, Lucia; Ferrari, Anna; Rivasi, Francesco; Forni, Flavio; Vandelli, Maria Angela
Aim: In order to increase the knowledge on the use of nanoparticles (NPs) in brain targeting, this article describes the conjugation of the sequence 12–32 (g21) of leptin to poly-lactide- co -glycolide NPs. The capability of these modified NPs to reach the brain was evaluated in rats after intravenous administration.Materials & Methods: The g21 was linked on the surface of NPs labeled with tetramethylrhodamine by means of the Avidin-Biotin technology. The g21-labeled NPs were injected into the tail vein of rats and, after animal sacrifice, the brain localization was evaluated by confocal microscopy, fluorescence microscopy and electron microscopy. Studies to evaluate the biodistribution of the g21-modified NPs in comparison to the unmodified NPs were also carried out. Moreover, to confirm the absence of any anorectic effect of g21 linked on the surface of NPs, appropriate studies were used to assess the rats.Results: After intravenous administration, the g21-modified NPs were able to cross the blood–brain barrier and to enter the brain parenchyma. The biodistribution studies of both unmodified and modified NPs pointed out an uptake at liver and spleen level, whereas only the g21-modified NPs showed brain localization. The food-intake experiments pointed out that the intravenous administration of g21 conjugated to the NP surface did not produce any anorectic effect in the rats.Conclusion: g21-modified NPs were able to cross the blood–brain barrier. These new modified NPs could be effectively considered as useful carrier systems for brain drug delivery. Original submitted: 27/11/2010; Revised submitted: 09/03/2011